Vaccine Inoculation Route Modulates Early Immunity and Consequently Antigen-Specific Immune Response - Rosenbaum, Pierre; Tchitchek, Nicolas; Joly, Candie; Rodriguez Pozo, André; Stimmer, Lev; Langlois, Sébastien; Hocini, Hakim; Gosse, Leslie; Pejoski, David; Cosma, Antonio; Beignon, Anne-Sophie; Dereuddre-Bosquet, Nathalie; et al. (Frontiers in Immunology, 2021)
Vaccination is one of the most efficient public healthcare measures to fight infectious diseases. Nevertheless, the immune mechanisms induced in vivo by vaccination are still unclear. The route of administration, an important vaccination parameter, can substantially modify the quality of the response. How the route of administration affects the generation and profile of immune responses is of major interest. Here, we aimed to extensively characterize the profiles of the innate and adaptive response to vaccination induced after intradermal, subcutaneous, or intramuscular administration with a modified vaccinia virus Ankara model vaccine in non-human primates. The adaptive response following subcutaneous immunization was clearly different from that following intradermal or intramuscular immunization. The subcutaneous route induced a higher level of neutralizing antibodies than the intradermal and intramuscular vaccination routes. In contrast, polyfunctional CD8+ T-cell responses were preferentially induced after intradermal or intramuscular injection. We observed the same dichotomy when analyzing the early molecular and cellular immune events, highlighting the recruitment of cell populations, such as CD8+ T lymphocytes and myeloid-derived suppressive cells, and the activation of key immunomodulatory gene pathways. These results demonstrate that the quality of the vaccine response induced by an attenuated vaccine is shaped by early and subtle modifications of the innate immune response. In this immunization context, the route of administration must be tailored to the desired type of protective immune response. This will be achieved through systems vaccinology and mathematical modeling, which will be critical for predicting the efficacy of the vaccination route for personalized medicine.